TH17 Cell and Epithelial Cell Crosstalk during Inflammatory Bowel Disease and Carcinogenesis - Kempski, Jan; Brockmann, Leonie; Gagliani, Nicola; Huber, Samuel (Frontiers in Immunology, 2017)
The intestine is colonized by hundreds of different species of commensal bacteria, viruses and fungi. Therefore, the intestinal immune system is constantly being challenged by foreign antigens. The immune system, the commensal microbiota and the intestinal epithelial surface have to maintain a tight balance to guarantee defense against potential pathogens and to prevent chronic inflammatory conditions at the same time. Failure of these mechanisms can lead to a vicious cycle in which a perpetual tissue damage/repair process results in a pathological reorganization of the normal mucosal surface. This dysregulation of the intestine is considered to be one of the underlying cause for both inflammatory bowel disease (IBD) and colorectal cancer (CRC). TH17 cells have been associated with immune-mediated diseases, such as IBD, since their discovery in 2005. Upon mucosal damage, these cells are induced by a combination of different cytokines, such as IL-6, TGF-β, and IL-1β. TH17 cells are crucial players in the defense against extracellular pathogens and have various mechanisms to fulfil their function. They can activate and attract phagocytic cells. Additionally, TH17 cells can induce the release of anti-microbial peptides from non-immune cells, such as epithelial cells. The flip side of the coin is the strong potential of TH17 cells to be pro-inflammatory and promote pathogenicity. TH17 cells have been linked to both mucosal regeneration and inflammation. In turn, these cells and their cytokines emerged as potential therapeutic targets both for inflammatory diseases and cancer. This review will summarize the current knowledge regarding the TH17 cell-enterocyte crosstalk and give an overview of its clinical implications.